The determinants of cash waqf giving behaviour in Negeri Sembilan / Siti Aisyah Abdul Kadir - Abdul Kadir, Siti Aisyah (Faculty of Business Management, University Teknologi MARA, 2018)
Cash waqfis a movable waqfthat has been established with liquid money or in the other word waqfby using a cash or money. Typically, waqf usually focus on the real asset property such as building and land, but not many people have all those assets to contribute in waqf, therefore cash waqfhas become as an alternative for those individuals who does not have such immovable asset but only have movable asset such as cash. Because of that, any individuals can do a charity in form ofwaqfas long as they want in order to get blessing form Allah S WT. In Malaysia, cash waqf have been implemented for a number of years and might have a potential to promote the development of ummah but unfortunately, its development is still infancy. Given that, the aim of this study is to examine the factors influence cash waqf giving behaviour among Muslim in Negeri Sembilan and to identify which factors influence the most. The factors involved in this study are religiosity, knowledge and trustworthiness. The data of the study are collected by using questionnaire where 150 of questionnaires have been distributed to the respondent. The statistical method used for data analysis is regression, correlation and reliability. Overall, at the end of this study, the result has shown there is only two independent variables that are significant with the dependent variables that is religiosity and trustworthiness while knowledge is not significant.